Better Business by DesignTM: Introduction to the SOPHIC Conceptual Model. (September 2017) - Rando, Cynthia; Fogarty, Jennifer
The SOPHIC Conceptual Model (SCM) introduces a unique approach to human centered design through the role of a Trade Space Negotiator (TSN) and a focus on convergence of three distinct domains: Business Strategy, Human Factors and Engineering. Each domain has significant contributions and a unique perspective that needs to be considered to find the optimum balance for the organization to deliver successful products or services. The function of the TSN is to find this balance between the seemingly competing domains for the organization. The SCM and TSN work together to prevent and resolve conflict by identifying discordance between the domains and converge on an integrated solution resulting in innovative outcomes. When the business is optimized through the SOPHIC Conceptual Model it delivers a successful user interaction, addresses tangible needs, and delivers a positive experience resulting in cost effective processes and innovative outcomes leading to Better Business by Design TM .